2012
DOI: 10.1128/jvi.00682-12
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1R Signaling Is Essential for Induction of Proapoptotic CD8 T Cells, Viral Clearance, and Pathology during Lymphocytic Choriomeningitis Virus Infection in Mice

Abstract: gThe T cell granule exocytosis pathway is essential to control hepatotropic lymphocytic choriomeningitis virus strain WE (LCMV-WE) but also contributes to the observed pathology in mice. Although effective antiviral T cell immunity and development of viral hepatitis are strictly dependent on perforin and granzymes, the molecular basis underlying induction of functionally competent virus-immune T cells, including participation of the innate immune system, is far from being resolved. We demonstrate here that LCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
(73 reference statements)
4
17
1
Order By: Relevance
“…For example, IL-1R1−/− mice were more susceptible to respiratory influenza virus infection (influenza virus strain PR8) and showed both a markedly reduced IgM response and impaired recruitment of CD4 + T cells to the site of infection (4). IL-1R1−/− mice infected with lymphocytic choriomeningitis virus (LCMV) also exhibited reduced expansion and proliferation of virus-specific CD8 + T cells and an inability to clear LCMV compared to WT control mice (31). …”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-1R1−/− mice were more susceptible to respiratory influenza virus infection (influenza virus strain PR8) and showed both a markedly reduced IgM response and impaired recruitment of CD4 + T cells to the site of infection (4). IL-1R1−/− mice infected with lymphocytic choriomeningitis virus (LCMV) also exhibited reduced expansion and proliferation of virus-specific CD8 + T cells and an inability to clear LCMV compared to WT control mice (31). …”
Section: Discussionmentioning
confidence: 99%
“…Besides granzyme A and granzyme B, only GzmK is expressed in WT-derived CTL cells (Figure 5a), as we have previously reported. 16,27 Overall, no induction or perturbation in the expression of other granzymes was detected in Gzmk − / − CTL, suggesting that absence of GzmK is not balanced by alterations in production of other granzymes.…”
Section: Absence Of Gzmk Does Not Affect Expression Of Other Granzymementioning
confidence: 94%
“…(Joeckel et al, 2012)) and tumors (Ghiringhelli et al, 2009). Using the OT-1 model, it has recently reported that IL-1β results in increased numbers and effector function of antigen-specific T cells.…”
Section: Orchestration Of Innate and Adaptive Immunocompetent Cellsmentioning
confidence: 99%